Manifestations of bureaucracy in Iraq's educational institution (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study, titled (manifestations of bureaucracy in Iraq’s educational institution) seeks toidentify the mechanism of administrative work of the bureaucratic organization in theeducational institution, and how it manages the work in terms of its orientations and the extent ofits efficiency and quality in the completion of administrative work in the institution. The studyfound the following:1- Government institutions, especially our educational institutions, need to reconsider theorganization of institutional work and end cases of mediation and nepotism withineducational institutions.2- Working on selecting leaders within the institution on the basis of efficiency, quality andacademic qualifications.As for the study’s recommendations, theseinclude:1- The necessity of working to run awareness sessions for workers in higher education andscientific research institutions, each according to his/her specialization, academicqualifications and field of work.2- The need to redouble efforts by administrative leaders in institutions of higher educationand scientific research in order to reform the work of the ministry and its affiliatedinstitutions.